On the Effect of a DC Electric Field on Soot Particles' Emission of a Laminar Diffusion Flame. Issue 1 (2nd January 2022) - Sayed-Kassem, Ahmad; Gillon, Pascale; Idir, Mahmoud; Gilard, Virginie
ABSTRACT: Electric fields were proved to affect combustion stability, flame form, and pollutant emissions. The influence of the electric field on soot formation and growth is still an open topic. In this context, the effect of an external electric field on a 67 mm laminar diffusion flame was studied and ethylene was used as well-suited fuel to investigate soot formation and growth. The flame was placed under a uniform high voltage difference and laser Extinction/Scattering techniques were employed to monitor soot volume fraction, particles' diameter and particles' number concentration at different locations in the flame body. Interestingly, when a potential of 8 kV was applied, the flame appeared to be shorter and larger, soot volume fraction diminished whilst the particles' diameter increased under the effect of the electric field. The ionic wind is considered the main cause of the geometrical modifications of the flame due to the increase in the burning rate and the acceleration of charged species. It was, besides the action of the electric field on the growth mechanism, the plausible source for the soot formation variation in the flame.